A 1 × 64 Complementary Metal Oxide Semiconductor ranging sensor based on Current-Assisted Photonic Demodulators. (20th November 2008) - Van Der Tempel, Ward; Van Nieuwenhove, Daniel; Grootjans, Riemer; Kuijk, Maarten
A new Complementary Metal Oxide Semiconductor (CMOS) active pixel-ranging sensor is presented, realised as a 1 × 64 array of 30 µm × 30 µm lock-in pixels. The sensor is based on the Current-Assisted Photonic Demodulator (CAPD), implemented in a Standard CMOS 0.35 µm technology. The ranging pixel achieves 75% Fill-Factor, 0.22 A W−1 total QE and a demodulation bandwidth up to 70 MHz, both at 860 nm light. Range-finding is achieved through Modulated Wave Time-Of-Flight (TOF) measurements with a modulation frequency of 20 MHz. Distance measurements are presented. This sensor represents the first step towards integrating CAPD-based lock-in pixels in large TOF CMOS ranging systems.